Comparison of the effectiveness of breast milk, dry-keeping, and use of chlorhexidine in umbilical cord care - Emine Ela Küçük; Dilek Küçük Alemdar; Kürşad Yapar; Şahin Direkel; Nejla Ömerbeyoğlu; Ülker Başak (Acta Clinica Croatica)
This research was conducted as a randomized study with the objective of determining the effects of breast milk, dry-keeping, and chlorhexidine methods used in umbilical cord care on the time of umbilical cord separation and on omphalitis and bacterial flora development. The study was carried out in 97 newborns divided into three groups, as follows: breast milk was used for umbilical cord care in group 1 of 32 newborns, dry-keeping was applied in group 2 of 35 newborns, and chlorhexidine was applied in group 3 of 30 newborns. Infants were assigned to three subgroups through randomization performed using a computer program. Swabs for culture were obtained from umbilical cord on postnatal day 2 and day 5. While difference in the results of the care methods applied was notsignifi cant on day 2, significant difference in the results was found on day 5. It was determined that there was no bacterial growth in 46.7% of the chlorhexidine group, while maximum bacterial growth was recorded in the dry-keeping group. In the chlorhexidine group, timing of umbilical cord separation was significantly shorter than in other groups. Study results indicated that the most effective method was the use of chlorhexidine. Dry-keeping can be risky since it was inefficient in preventing umbilical colonization, and in cases where the cost of chlorhexidine is an issue, the use of breast milk can be recommended.